Homer and Hesiod in the 4th Century C.E.: an Hesiodic Quotation (Op. 412) in Himerius (Or. LXXIV, 2-3) - Muñoz Llamosas, Virginia (Cuadernos de Filología Clásica. Estudios griegos e indoeuropeos, 2013)
The aim of this article is to analyze Himerius’ use of Hesiodic words μελέτη δέ τοι ἔργον ὀφέλλει (Op. 412). Himerius does not mention Hesiod, but says these words belong to a «distinguished poet». This lack of information about the author could be explained by Himerius’ ignorance of the author of his quotation or by a confusion with Homer. To answer to this question we will examine fi rst the quotation itself and its other occurrences in Greek Literature; then, how does Himerius quote other authors and which authors are quoted by him. Finally, we will explore the possibility of a confusion between Homer and Hesiod and their reception in antiquity.